Synthesis and characterization of samarium-cobalt-trioxide perovskite catalyst for the kinetic and longevity studies of methane dry reforming - Osazuwa, Osarieme Uyi (2017)
The alarming rate of global warming necessitates the utilization of greenhouse gases such as methane (CH4) and carbon dioxide (CO2). One of such propositions is methane dry reforming. Methane dry reforming requires the use of heterogeneous catalyst due to its strong endothermicity. Several catalysts have been employed for methane dry reforming with catalyst deactivation as the major drawback. In the present study, samarium cobalt trioxide (SmCoO3) perovskite catalyst has been applied for methane dry reforming. The reduced affinity of cobalt (Co) for carbon and the rich oxygen (O2) storage capacity of samarium oxide (Sm2O3) are responsible for the choice of this catalyst. The SmCoO3 perovskite catalyst was synthesized using the sol-gel citrate method with samarium (Sm) occupying the ‗A‘ site and Co occupying the ‗B‘ site. The Goldschmidt tolerance model was employed to obtain a tolerance factor of 0.96 for the SmCoO3 perovskite structure. X-ray diffraction confirmed a monophasic crystalline structure for the synthesized SmCoO3. Temperature programmed desorption showed net-acidic catalytic site strength. Energy dispersive X-ray and X-ray photoelectron spectroscopy confirmed the elemental and chemical composition of the synthesized SmCoO3 perovskite. Prior to the kinetic modelling, the effects of temperature (ranged 873 - 1173 K), feed ratio (0.5 – 2.0) and partial pressure (ranged 6.8 – 60.8 kPa) were studied. Results from the studies showed that conversion of reactants were above 90% and products yield were above 60%, at 1073 K. The kinetics data acquired were fitted into the power law and Langmuir–Hinshelwood model. Activation energy of 41 kJ mol-1 and 25 kJ mol-1 were obtained from the power law model for CH4 and CO2, respectively. Further studies using the Langmuir-Hinshelwood model gave activation energy of 44 kJ mol-1 and 22 kJ mol-1 for CH4 and CO2, respectively. The longevity of the catalyst was tested in a feed ratio range of 0.5 – 2.0 at 1073 K, for 72 h. Reactions at 0.75, 1.0 and 1.33 feed ratios had very good stability. The spent SmCoO3 perovskite catalyst, characterized by field emission scanning electron microscope, energy dispersive X-ray, temperature programmed oxidation, Fourier transform infrared spectroscopy, transmission electron microscope and X-ray photoelectron spectroscopy techniques showed evidence of whisker carbon species which did not deactivate the catalyst. The carbon was gasified by the dual oxygen species present in the SmCoO3 perovskite as evident in the X-ray photoelectron spectroscopy analysis. The reducibility of the Co species as evident in the TPR analysis enhanced the performance of the SmCoO3 perovskite catalyst. These properties are responsible for the superior performance of SmCoO3 perovskite catalyst over various metallic catalysts previously reported.